2020
DOI: 10.22435/jtoi.v13i1.1887
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Tanaman Obat Oleh Masyarakat Suku Melayu Di Kabupaten Sambas

Abstract: ABSTRACT Medicinal plant was used to solve the health problems by community both for prevention and medication. The medicinal plants utilization has a pivotal role on the sustainability and biodiversity of plants. Sambas Regency of West Kalimantan is dominated mostly by Malay ethnicity. They have different perspective in medicinal plants utilization, using a system of religion and belief that is continuously handed down from generation to generation. The study aims to analyze the patterns of medicinal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
1
2
0
14
Order By: Relevance
“…Fever in the Rejang ethnic can be treated by using 15 plant species, similar research results were also found in the Malays in Sambas that from233 plant species, there are 103 groups of diseases treated in this ethnic, fever is one of the groups with the highest score using medicinal plants together with utilization for antibiotics, smallpox, and so forth [40]. Many types of plants that have been invested can treat fever because it may be that the local people are often attacked by this disease.…”
Section: Types Of Diseases Found In the Serawai Ethnic Groupsupporting
confidence: 65%
“…Fever in the Rejang ethnic can be treated by using 15 plant species, similar research results were also found in the Malays in Sambas that from233 plant species, there are 103 groups of diseases treated in this ethnic, fever is one of the groups with the highest score using medicinal plants together with utilization for antibiotics, smallpox, and so forth [40]. Many types of plants that have been invested can treat fever because it may be that the local people are often attacked by this disease.…”
Section: Types Of Diseases Found In the Serawai Ethnic Groupsupporting
confidence: 65%
“…Beberapa wilayah di Kalimantan Barat telah tercatat laporan penggunaan tumbuhan obat seperti di Desa Pengadang Kabupaten Sanggau [2], Desa Kelam Sejahtera, Merpak, dan Kebong Kabupaten Sintang [3] [4], Desa Sungai Baru, Sungai Serabek, dan Tekarang Kabupaten Sambas [5], Desa Tonang Kabupaten Landak [6], Desa Sepandan dan Lanjak Besar Kabupaten Kapuas Hulu [7], Desa Masbangun Kabupaten Kayong Utara [8] dan Desa Tapang Semadak Kabupaten Sekadau [9]. Pemanfaatan tumbuhan obat tersebut oleh beragam suku seperti suku Melayu [2] [5], Dayak Iban [7], Dayak Kanayant [6], Dayak Paus [2], Dayak Daro' dan Bukat [10], Dayak Desa [4], dan Dayak Muara [11].…”
Section: Pendahuluanunclassified
“…Perbedaan suku menyebabkan perbedaan dalam pemanfaatan tumbuhan sebagai tumbuhan obat. Perbedaan tersebut p-ISSN : 2528-3561 e-ISSN : seperti dilaporkan oleh ref [5], dimana Suku Melayu yang ada di tiga desa di Kabupaten Sambas telah memanfaatkan sebanyak 233 jenis tumbuhan obat. Sementara itu, menurut ref.…”
Section: Pendahuluanunclassified
“…Masyarakat di Kalimantan Barat memiliki beragam kearifan lokal dalam memanfaatkan tumbuhan obat, baik dari aspek suku (Pranaka et al, 2020;Sari et al, 2021;(Yusro et al, 2020a) aspek kelompok penyakit (Ardiana et al, 2019;Rania et al, 2019; ataupun aspek kewilayahan seperti desa ataupun wilayah sekitar hutan (Aminah et al, 2016;Sauji et al, 2019;. Kearifan lokal tersebut perlu untuk dipertahankan agar tidak hilang pada masa yang akan datang, dan untuk wilayahwilayah lain di Kalimantan Barat yang belum dilakukan kajian perlu untuk dikaji keragaman kearifan lokal yang mereka miliki.…”
Section: Pendahuluanunclassified